Perawatan, tunjangan cacad, dan uang duka pegawai negeri sipil : Surat edaran bersama Menteri Kesehatan dan Kepala Badan Administrasi Kepegawaian Negara nomor 368/Men Kes/EB/VII/1981, nomor 09/SE/1981 tanggal 7 Juli 1981 (Badan Administrasi Kepegawaian Negara, 1981)
Circular letter of the Civil Servants Administrative Agency and the Minister of Health to government employees regarding nursing care, aid for disabled, and funds given to an employee's family at his death.